2018
DOI: 10.1002/jcb.27938
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylated in cancer 1 (HIC1) suppresses bladder cancer progression by targeting yes‐associated protein (YAP) pathway

Abstract: Objectives Bladder cancer (BCa) is the most common malignant tumor in the urinary system. Growing evidence suggests that as a tumor suppressor gene, hypermethylated in cancer 1 (HIC1) is correlated with various malignancies in the modulation of tumor progression. This study aims to investigate the effect of HIC1 on regulating the proliferation, migration, and invasion of BCa. Methods Quantitative reverse transcription polymerase chain reaction (qRT‐PCR) and Western blot (WB) were used to evaluate the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Hic1 is often found to be epigenetically silenced in various types of human cancers (Wales et al, 1995;Chen et al, 2003); hence, it is considered to be a key player in cancer progression and proliferation (Zheng et al, 2012). Consistent with a recent study demonstrating that the downregulation of Hic1 promoted cell proliferation, whereas overexpression of Hic1 inhibited cell proliferation (Zhou et al, 2019), Hic1 deletion in smooth muscle cells in our study resulted in their increased proliferation, leading to the development of enlarged seminiferous tubules that were surrounded by a larger number of PMCs. In rodents, proliferation of PMCs and Sertoli cells ceases at ∼2 weeks of age, concomitantly with secretion of luminal fluid and entry into meiosis (Setchell, 1970;Orth, 1982;Rato et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…Hic1 is often found to be epigenetically silenced in various types of human cancers (Wales et al, 1995;Chen et al, 2003); hence, it is considered to be a key player in cancer progression and proliferation (Zheng et al, 2012). Consistent with a recent study demonstrating that the downregulation of Hic1 promoted cell proliferation, whereas overexpression of Hic1 inhibited cell proliferation (Zhou et al, 2019), Hic1 deletion in smooth muscle cells in our study resulted in their increased proliferation, leading to the development of enlarged seminiferous tubules that were surrounded by a larger number of PMCs. In rodents, proliferation of PMCs and Sertoli cells ceases at ∼2 weeks of age, concomitantly with secretion of luminal fluid and entry into meiosis (Setchell, 1970;Orth, 1982;Rato et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…Although Negraes et al Aberrant DNA Methylation in Bladder Cancer Siddiqui, Yaqinuddin have previously reported the hypermethylation of SFN gene in BC, 16 but due to its indistinct hypermethylation pattern in both cancerous and control group, it was not considered favorable for biomarker for BC detection. Similarly, silencing of HIC1 gene due to methylation of their promoter regions has been reported in multiple human cancer types including BC 17 but no significant results were reported in BC to date. In contrast, our study has revealed significant DNA hypermethylation of both SFN and HIC1 genes making them promising biomarkers for BC patients in Saudi Arabia.…”
Section: Resultsmentioning
confidence: 97%
“…2 D), and its well-known tumor suppressor gene plays a critical role in various cancers [ 19 ]. One study has been shown, that HIC1 inhibits cell growth and migration via regulating YAP pathway in BC [ 20 ], thus we chose HIC1 for the further study. To replicate this finding, we used quantitative RT-PCR (qRT-PCR) and Western blotting to determine the expression levels of HIC1 in ZBTB7A knockdown cells.…”
Section: Resultsmentioning
confidence: 99%
“…In bladder cancer, the promoter of HIC1 existed methylation statuses and the expression of HIC1 was downregulated in BC [ 19 , 33 , 34 ]. HIC1 was reported to inhibit cancer progression via targeting the Yap pathway in BC [ 20 ]. Similarly, our data showed that HIC1 expression was decreased in BC tissues and knockdown of HIC1 promoted cell growth and migration.…”
Section: Discussionmentioning
confidence: 99%